Pengaruh Pendidikan Kewirausahaan dan Lingkungan Keluarga Terhadap Minat Berwirausaha Mahasiswa STKIP PGRI Jombang - Wahyuningsih, Roy (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2020)
This study is aimed to analize the influence of entrepreneurial education and family environment on the entrepreneurial interest of students at STKIP PGRI Jombang. The research method used in this research was a quantitative statistical approach. The population consisted of 6 classes with a total of 266 students who were taken by purposive sampling technique randomly so that the sample amounted to 44 students. Validity test and reliability test were used for instrument testing. This research was conducted by distributing questionnaires to students at STKIP PGRI Jombang who had taken entrepreneurship courses. The data analysis technique used multiple linear regression analysis in the SPSS 20.00 program. The results of the study showed that there was a significant influence between the entrepreneurial education variable (X1) and the family environment (X2) on the students’ interest in entrepreneurship (Y).